On the Use of Permutation Tests in the Analysis of the Factorial Design of Experiment Results - Złotoś, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
An experimental design is one of the tools which are used in statistical quality control. The proper implementation of experimental design results in the improvement of technological outcomes of a manufacturing process, which in turn leads to the enhancement of economic results. Permutation tests, among other things, form a group of resampling methods which are used to verify statistical hypotheses. These tests, unlike parametric ones, do not entail the fulfilment of strict criteria and may be used for a small number of observations. The presented article deals with the use of permutation tests in the design of experiments. The proposed method will be presented with reference to selected empirical data.